Aminolevulinic Acid-Photodynamic Therapy Combined with Topically Applied Vascular Disrupting Agent Vadimezan Led to Enhanced Antitumor Responses - Marrero, Allison (2011)
The tumor-vascular disrupting agent (VDA) vadimezan (5,6-dimethylxanthenone-4-acetic acid, DMXAA) has been shown to potentiate the antitumor activity of photodynamic therapy (PDT) using systemically administered photosensitizers. Here, we characterized the response of subcutaneous syngeneic Colon26 murine colon adenocarcinoma tumors to PDT using the locally applied photosensitizer precursor aminolevulinic acid (ALA) in combination with a topical formulation of vadimezan. Diffuse correlation spectroscopy (DCS), a non-invasive method for monitoring blood flow, was utilized to determine tumor vascular response to treatment. Additionally, correlative CD31-immunohistochemistry to visualize endothelial damage, ELISA assays to measure induction of tumor necrosis factor-alpha (TNF-α) and tumor weight measurements were also examined in separate animals. In our previous work, DCS revealed a selective decrease in tumor blood flow over time following topical vadimezan. ALA-PDT treatment also induced a decrease in tumor blood flow. The onset of blood flow reduction was rapid in tumors treated with both ALA-PDT and vadimezan. CD31-immunostaining of tumor sections confirmed vascular damage following topical application of vadimezan. Tumor weight measurements revealed enhanced tumor growth inhibition with combination treatment compared to ALA-PDT or vadimezan treatment alone. In conclusion, vadimezan as a topical agent enhances treatment efficacy when combined with ALA-PDT. This combination could be useful in clinical applications.